2003
DOI: 10.1161/01.hyp.0000048862.28501.72
|View full text |Cite
|
Sign up to set email alerts
|

CYP450- and COMT-Derived Estradiol Metabolites Inhibit Activity of Human Coronary Artery SMCs

Abstract: Abstract-The purpose of this study is to test the hypothesis that the inhibitory effects of estradiol in human coronary vascular smooth muscle cells are mediated via local conversion to methoxyestradiols via specific cytochrome P 450s (CYP450s) and catechol-O-methyltransferase (COMT). The inhibitory effects of estradiol on serum-induced cell activity (DNA synthesis, cell number, collagen synthesis, and cell migration) were enhanced by 3-methylcholantherene, phenobarbital (broad-spectrum CYP450 inducers), and ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
49
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 21 publications
5
49
0
Order By: Relevance
“…Previously, using pharmacological agents to block or induce the conversion of estradiol to hydroxyestradiols and methoxyestradiols, we provided indirect evidence that methoxyestradiols mediate the vascular antimitogenic effects of estradiol. 5,13 We found similar evidence for this hypothesis in cardiac fibroblasts 14 and glomerular mesangial cells. 15 Although use of pharmacological agents provides evidence supporting our hypothesis, direct evidence for the role of methoxyestradiols as mediators of the ER-independent antimitogenic actions of estradiol is lacking.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Previously, using pharmacological agents to block or induce the conversion of estradiol to hydroxyestradiols and methoxyestradiols, we provided indirect evidence that methoxyestradiols mediate the vascular antimitogenic effects of estradiol. 5,13 We found similar evidence for this hypothesis in cardiac fibroblasts 14 and glomerular mesangial cells. 15 Although use of pharmacological agents provides evidence supporting our hypothesis, direct evidence for the role of methoxyestradiols as mediators of the ER-independent antimitogenic actions of estradiol is lacking.…”
supporting
confidence: 79%
“…13 We have demonstrated that ICI182,780 blocks the vascular antimitogenic effects of estradiol only at concentrations that inhibit the metabolism of estradiol to hydroxyestradiols. 5,13 The above findings suggest that the antiproliferative actions of estradiol are ER-independent. Because estradiol is sequentially metabolized to hydroxyestradiols by CYP450s and hydroxyestradiols are methylated to methoxyestradiols by COMT, we hypothesize that methoxyestradiols mediate the antiproliferative actions of estradiol on SMCs via ER-independent mechanisms.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Sequential metabolism of estradiol to catecholestradiols and ultimately to methoxyestradiols is responsible for the antimitogenic effects of estradiol on vascular SMCs, 61 cardiac fibroblasts, 62 and glomerular mesangial cells. 63 Importantly, these effects of estradiol appear to be ER-independent.…”
Section: Type Of Estrogenmentioning
confidence: 99%
“…63 Importantly, these effects of estradiol appear to be ER-independent. [61][62][63] The antimitogenic effects of estradiol are lost in aortic SMCs cultured from catecholamine-O-methyltransferase (COMT) knockout mice that cannot convert estradiol to 2-methoxyestradiol. 64 Increased proliferation of SMCs, cardiac fibroblasts, and mesangial cells lead to hypertension, vascular disease, left ventricular hypertrophy, and glomerulosclerosis.…”
Section: Type Of Estrogenmentioning
confidence: 99%